A Decade of Progress, A Decade of Frustration - Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
The past decade has seen tremendous research progress for the northern bobwhite (Colinus virginianus). Research conducted during the 1990s advanced our understanding of bobwhite breeding biology, habitat relationships, long-term population trends, and genetics, among other things. Technological advances allowed improvements in censusing techniques, tracking broods, assessing population status in relation to broad scale land use changes, and identifying nest predators. The 1990s also saw the development of a National Strategic Plan for Quail Management and Research, the emergence of the Southeast Quail Study Group, and a renewed interest in National Quail Symposia. Despite this recent renaissance in research and related activities, bobwhite population declines continued throughout much of the southeastern United States and elsewhere. There is a palpable level of frustration among quail hunters, resource agency managers, and other quail enthusiasts who feel that: (1) seemingly nothing is being done to reverse the bobwhite population decline, and (2) that the scientific community has not developed a meaningful or realistic research agenda. It is an amazing paradox that we have made great bobwhite research progress during the past decade, but virtually none of the new insights gained from research have been successfully applied, on the ground, to improve bobwhite numbers. I hypothesize that the disconnect between recent scientific advances, and management applications to reverse the bobwhite decline, is a function of numerous cultural and economic factors that will be difficult to overcome. These factors include: (1) broad scale land use trends that are hostile to the production and maintenance of wild bobwhite populations, (2) habitat management and maintenance costs that are beyond the reach of most resource agencies and individuals, and (3) lack of incentives to motivate individuals and organizations to tackle bobwhite management on a meaningful scale. Whether land use planning, land management policy, and/or market incentives can conspire to provide useable habitat space through time for bobwhites (and other quails) on a scale that will be sufficient to reverse widespread population declines, is one of the most vexing wildlife management problems for the next century.
Keywords: Colinus virginianus; incentives; management; northern bobwhite; philosophy; research